A RARE ENCOUNTER: LISTERIA MONOCYTOGENES AND BRAIN ABSCESS - Khanum, Iffat; Ishrat, Ibtesam; Haroon, Ammara; Zafar, Amara (Journal of Ayub Medical College Abbottabad, 2025)
Listeriosis, caused by Listeria Monocytogenes, is a serious yet rare illness caused by consuming contaminated food and is considered a global public threat. Central nervous system (CNS) involvement often follows bacteraemia; common clinical presentation is usually meningitis. Listeria brain abscess is an uncommon pathology and can manifest in various clinical presentations, with fever and focal neurological deficits being the most common. Brain abscess secondary to listeria is associated with high mortality. We present a rare case of a 68-year-old immunocompromised female who developed a cerebral abscess due to Listeria monocytogenes. The presence of fever, increased somnolence prompted further investigation. This case underscores the need for brain imaging in the evaluation of listeria sepsis, even when clinical presentations are atypical. Additionally, in cases without major neurological deficits or swelling, postponing abscess drainage may be considered. A cautious approach with IV antibiotics, repeat imaging and close monitoring can be offered to patients who are unwilling to undergo aspiration and drainage of brain abscess or are poor surgical candidates.